PEMANFAATAN MEDIA SOSIAL YOUTUBE SEBAGAI MEDIA PROMOSI PERPUSTAKAAN DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN KUBU RAYA - Rahmadani, Riska; Sahidi, Sahidi; Rahman, Mifta (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The popularity of social media has been used by organizations to carry out promotional activities, including libraries. Currently, many libraries use social media for promotional activities because of the various benefits that can be achieved, including Dinas Perpustakaan dan Kearsipan Kabupaten Kubu Raya. The purpose of this study is to determine the implementation of promotional activities carried out by Dinas Perpustakaan dan Kearsipan Kabupaten Kubu Raya through Youtube and the perceived obstacles in its implementation. This research uses a qualitative research approach. Observations and in-depth interviews uses to collect data. Data analysis techniques begin with data reduction, followed by the presentation of data, finally drawing conclusions. The data validity test is to use triangulation techniques. The results showed that Dinas Perpustakaan dan Kearsipan Kabupaten Kubu Raya has carried out promotional activities by paying attention to four social media marketing factors: 1) Content creation is carried out by creating creative content that shows the characteristics of Dinas Perpustakaan dan Kearsipan Kabupaten Kubu Raya and the services available therein; 2) Content sharing is carried out by sharing content uploaded on Youtube to other media platforms and cross-checking the content to be shared; 3) Connecting is done by spreading content uploaded through other social media to expand connections; 4) Community building is done by joining a community that has the potential to utilize the library. The obstacles faced are the lack of Human Resources to manage promotional content and the limited facilities used to create promotional content.